Some printing parameters affecting the screw withdrawal strength of materials used in joints developed in 3D printers for furniture - Uysal, Mesut (DergiPark, 2024)
This study examined to benchmark the screw withdrawal strength (SWS) of the 3D-printed PLA materials considering various infill patterns and ratios. SWS is one of the critical material properties for furniture joints. For this purpose, dimensions of 10 × 50 × 50 mm specimens made of PLA+ were printed according to ASTM D 6117-18. Three infill patterns (line, grid, and concentric) and four infill ratios (25%, 50%, 75%, and 100%) were used as printing parameters to construct a complete 3 × 4 factorial experiment. According to the results, line infill patterns had the highest density compared to the grid and concentric patterns for all infill ratios. Concentric infill patterns with an infill ratio of 100% (108.41 MPa) had the greatest SWS. Grid infill patterns provided higher strength at the lower infill ratios than line and concentric infill patterns. Here, diffusion for interfaces of strands affected the SWSs of the 3D-printed materials. This study would provide insight into the 3D-printed joints in the field of furniture mechanics. © 2024, DergiPark. All rights reserved.
Mobilyalar için 3B yazıcılarda geliştirilen birleştirmelerde kullanılan malzemenin vida tutma kapasitesini etkileyen bazı baskı parametreleri
Keywords: 3D printing; Furniture joint; Polylactic acid; Screw withdrawal strength